Reasons and remedies for the agglomeration of multilayered graphene and carbon nanotubes in polymers - Atif, Rasheed; Inam, Fawad (Beilstein journal of nanotechnology, 2016)
One of the main issues in the production of polymer nanocomposites is the dispersion state of filler as multilayered graphene (MLG) and carbon nanotubes (CNTs) tend to agglomerate due to van der Waals forces. The agglomeration can be avoided by using organic solvents, selecting suitable dispersion and production methods, and functionalizing the fillers. Another proposed method is the use of hybrid fillers as synergistic effects can cause an improvement in the dispersion state of the fillers. In this review article, various aspects of each process that can help avoid filler agglomeration and improve dispersion state are discussed in detail. This review article would be helpful for both current and prospective researchers in the field of MLG- and CNT-based polymer nanocomposites to achieve maximum enhancement in mechanical, thermal, and electrical properties of produced polymer nanocomposites.